Fundamentals of Management, Global Edition - Robbins, Stephen P.; Coulter, Mary A.; DeCenzo, David A.; Cenzo, David A. (Pearson International Content, 2019)
For undergraduate principles of marketing courses. Everything students need to know to develop their ‘management sense’ and be successful Fundamentals of Management covers the essential concepts of management by providing a solid foundation for understanding the key issues facing managers and organisations. The 11th Edition maintains a focus on learning and applying management theories, while now also highlighting opportunities to develop the skills in high demand by today’s employers. Fundamentals of Management offers an easy-to-understand, straightforward, and realistic approach to what works for managers and what doesn’t - with the ultimate goal to help students be successful in their careers. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.